2020
DOI: 10.1007/s42413-020-00078-3
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Theoretical Understanding of Placemaking

Abstract: Historically, planners, community development groups, and other place-engaged organizations and practitioners have worked to elevate the importance of place and placemaking in economically, socially, and environmentally responsible development. However, recent studies have presented the concept of placemaking from professionally different perspectives using a variety of definitions to both rationalize and operationalize this still somewhat nebulous concept. This ambiguity surrounding the term placemaking is fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
(46 reference statements)
1
33
0
Order By: Relevance
“…Therefore, this study subscribes to the premise that if the quality of urban open places can be predicted Fig. 3 Types of placemaking integrated into urban practices (Source: Adapted by Author from (Ellery et al, 2021;Wyckoff, 2014))…”
Section: Role Of Space Syntax In Analyzing the Spatial Attributes Of ...mentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, this study subscribes to the premise that if the quality of urban open places can be predicted Fig. 3 Types of placemaking integrated into urban practices (Source: Adapted by Author from (Ellery et al, 2021;Wyckoff, 2014))…”
Section: Role Of Space Syntax In Analyzing the Spatial Attributes Of ...mentioning
confidence: 92%
“…As shown in Fig. 3, four types of placemaking -standard, strategic, creative, and tactical -were categorized, as to be integrated into different urban practices (Ellery, Ellery, & Borkowsky, 2021;Wyckoff, 2014). "Standard" placemaking is the common term for promoting the quality of place and was created by the PPS.…”
Section: Integration Of Placemaking Approach In Urban Practicesmentioning
confidence: 99%
“…The concept of placemaking is understood differently by different disciplines, from cultural workers to architects (Ellery et al, 2021). For the purpose of this chapter, we tentatively define it as 'small-scale, citizen-informed … projects designed to improve, enliven and redefine the spaces of the city' (Sweeney et al, 2018) -or in our case, the spaces of the village, small town or local landscape.…”
Section: Placemaking As An Expression Of Community Well-beingmentioning
confidence: 99%
“…Project for public spaces (PPS) organization in 2013 has found that successful public spaces usually share four main qualities: being accessible, engaging people with physical and mental activities are comfortable, and have a positive image, in addition to being perceived as sociable spaces [ 16 ]. After evaluating thousands of open public spaces around the world, PPS developed a model that is called “The Place Making Model” as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%